Revision Patellar Tendon Reconstruction Using Hamstring Tendon Autograft - Estevao Santos MD; Wasif Islam MD; Michael Amick MD; Giscard J. Adeclat MD; Michael J. Medvecky MD (SAGE Publishing, 2024)
Background: Patellar tendon ruptures presenting in a chronic setting are rare events that impose technical surgical challenges due to proximal retraction of the patella, quadriceps muscle atrophy and contracture, and peripatellar adhesions. Various reconstruction techniques have been described using different grafts and fixation methods; however, there is a paucity of reported outcomes and there is no consensus on standard of care. Indications: The patient is a 36-year-old man who presented with a failed patellar tendon reconstruction 14 months after his initial surgery (performed 1 year after the initial injury) with functional weakness and loss of extension. The patient was indicated for a revision patellar tendon reconstruction due to persistent functional limitations. Technique Description: The revision patellar tendon reconstruction was performed with gracilis and semitendinosus tendon autografts harvested from the ipsilateral limb. Hardware was removed from the initial graft tunnels in the tibial tubercle and patella. Patellar height was estimated using fluoroscopic measurement of the contralateral patellar tendon length. The graft is first passed through the patellar tunnel, and the individual limbs of the graft are then both placed through the tibial tubercle tunnel. A sternal wire in a figure-of-eight configuration was used to progressively distalize the patella to match the native patellar height, and the graft was then tensioned and secured together. Results: The patient regained full range of motion at 2-year follow-up and was able to return to work and activities without functional limitations. Recent case series also using ipsilateral hamstring tendon autograft for chronic patellar tendon reconstruction report improved patient outcome scores, normal Insall-Salvati index, improved quadriceps strength, and high levels of patient satisfaction. Discussion/Conclusion: Chronic patellar tendon ruptures are technically challenging to treat, especially in the context of revision of a failed reconstruction. The technique presented in this video may aid orthopaedic surgeons in treating this rare but debilitating injury. Given the lack of high-quality evidence, future studies are needed to explore graft choices, graft fixation techniques, and postoperative protocols. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.